Proceedings of the International Conference on Recent Cognizance in Wireless Communication & Image Processing ICRCWIP-2014 - Afzalpulkar, Nitin; Srivastava, Vishnu; Singh, Ghanshyam; Bhatnagar, Deepak (Springer India : Imprint: Springer, 2016)
This volume comprises the proceedings of the International Conference on Recent Cognizance in Wireless Communication & Image Processing. It brings together content from academicians, researchers, and industry experts in areas of Wireless Communication and Image Processing. The volume provides a snapshot of current progress in computational creativity and a glimpse of future possibilities. The proceedings include two kinds of paper submissions: (i) regular papers addressing foundation issues, describing original research on creative systems development and modeling; and (ii) position papers describing work-in-progress or research directions for computational creativity. This work will be useful to professionals and researchers working in the core areas of wireless communications and image processing.